Efektivitas Saringan Abu Sekam Padi untuk Menurunkan Kekeruhan pada Air Sungai Martapura - Syarifudin A.; Imam Santoso (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2018)
Abstract: The Effectiveness of Rice Husk Ash Filter to Reduce Turbidity of Martapura River Water. Martapura River water is used by people living on riverbanks for cooking, washing, bathing, and others. The main problem of Martapura river water is the turbidity which is relatively high so it needs to be processed first before use. The preliminary test conducted on August 15, 2016 shows the value of turbidity of Martapura river water at 38.9 NTU. This research was an experimental research with the one group pretest and posttest design which aimed to determine the effectiveness of the filter to reduce the turbidity of Martapura river water. The medium used was rice husk ash with variation of thickness were 13 cm, 26 cm, and 39 cm. The effectiveness of filtration was determined by comparing the turbidity of water filtered with standards. The turbidity of Martapura river water before filtered was 35.7 NTU. After filtered by 13 cm, 26 cm and 39 cm filter, the turbidity of water decreased consecutive to 2.97 NTU, 1.17 NTU, and 0.95 NTU, with decreasing percentages respectively of 91.7%, 96.7% and 97.3%. All filtered water showed turbidity fulfilled both the standar of clean water and drinking water so that rice husk ash filter was effective decreased turbidity of Martapura river water. Filtered water is recommended to be cooked first to boil when used for drinking water because the number of bacteria of Coli has not been studied. Further research needs to be conducted by adding other parameters according to water quality standard